Versatile surface for solid–solid/liquid–solid triboelectric nanogenerator based on fluorocarbon liquid infused surfaces. Issue 1 (31st January 2020) - Chung, Jihoon; Cho, Handong; Yong, Hyungseok; Heo, Deokjae; Rim, You Seung; Lee, Sangmin
ABSTRACT: The triboelectric nanogenerator (TENG) is a recent mechanical energy harvesting technology that has been attracting significant attention. Its working principle involves the combination of triboelectrification and electrostatic induction. The TENG can harvest electrical energy from both solid–solid and liquid–solid contact TENGs. Due to their physical difference, triboelectric materials in the solid–solid TENG need to have high mechanical properties and the surface of the liquid–solid contact TENG should repel water. Therefore, the surface of the TENG must be versatile for applications in both solid–solid and liquid–solid contact environments. In this work, we develop a solid–solid/liquid–solid convertible TENG that has a slippery liquid-infused porous surface (SLIPS) at the top of the electrode. The SLIPS consists of a HDFS coated hierarchical Al(OH)3 structure and fluorocarbon liquid. The convertible TENG developed in this study is capable of harvesting electricity from both solid–solid and liquid–solid contacts due to the high mechanical property of Al(OH)3 and the water-based liquid repelling nature of the SLIPS. When the contact occurs in freestanding mode, electrical output was generated through solid–solid/liquid–solid sliding motions. The convertible TENG can harvest electricity from both solid–solid and liquid–solid contacts; thus, it can be a unified solution for TENG surface fabrication. Graphical abstract: uf0001